URGENSI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN PADA DUNIA PENDIDIKAN PERGURUAN TINGGI - Wafi Riqzullah H; M Farhan Frans Putra; Ahmad Mahardika; Rizki Rizaldi (CV. Adiba Aisha Amira, 2024)
The purpose of this research is to find out how the role of education in building the moral character students in the modern era. An effective value education system in schools is expected to be able to encourage students to be able to implement the values contained in the content of the subject matter invited by educators and be able to build good moral character. qualitative literature study research method obtained through the literacy process from various books, articles, and journals related to the material discussed. Conclusions that can be drawn from the role of education in building the moral character of students in the modern era. the need for structured planning of learning carried out in schools. It is necessary to make a new breakthrough system in terms of teaching as well as from the content of the material because it will be one of the bases for realizing the goals of civic education itself. When the system designed is effective, then the implementation of the content of the material presented by the educator will be well received by the students